2020
DOI: 10.1038/s41467-020-19248-0
|View full text |Cite
|
Sign up to set email alerts
|

Full genome viral sequences inform patterns of SARS-CoV-2 spread into and within Israel

Abstract: Full genome sequences are increasingly used to track the geographic spread and transmission dynamics of viral pathogens. Here, with a focus on Israel, we sequence 212 SARS-CoV-2 sequences and use them to perform a comprehensive analysis to trace the origins and spread of the virus. We find that travelers returning from the United States of America significantly contributed to viral spread in Israel, more than their proportion in incoming infected travelers. Using phylodynamic analysis, we estimate that the bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 41 publications
6
91
1
1
Order By: Relevance
“…We obtained 212 complete genomes (Fig 1B), mostly from samples with higher viral loads (Fig 1B). Consensus genomes had a median of 7 substitutions relative to the Wuhan-Hu-1/2019 reference sequence (range [4][5][6][7][8][9][10][11][12]. Phylogenetic analysis of whole consensus genomes identified 10 unique evolutionary lineages in our cohort (lineages determined by the PANGOLIN system, see Methods; Fig 1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained 212 complete genomes (Fig 1B), mostly from samples with higher viral loads (Fig 1B). Consensus genomes had a median of 7 substitutions relative to the Wuhan-Hu-1/2019 reference sequence (range [4][5][6][7][8][9][10][11][12]. Phylogenetic analysis of whole consensus genomes identified 10 unique evolutionary lineages in our cohort (lineages determined by the PANGOLIN system, see Methods; Fig 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Over the course of the SARS-CoV-2 pandemic, whole genome sequencing has been widely used to characterize patterns of broad geographic spread, transmission in local clusters, and the spread of specific viral variants [1][2][3][4][5][6]. Early reports demonstrated that SARS-CoV-2 exhibits genetic diversity within infected hosts, but this has been less studied than consensus-level genomic diversity [7].…”
Section: Introductionmentioning
confidence: 99%
“… 4 6 37 For example, if only 20% of the population were able to develop a sufficient viral load to infect others, then protective immunity in this subpopulation would be sufficient for an innocuous endemic equilibrium. 47 Furthermore, if seroconversion occurs largely in the subpopulation spreading the virus, 48 a sufficient herd immunity may only require a seroprevalence of around 10% of the effective population (right panel of figure 4 ). In short, one might challenge the assumption that COVID-19 is spread homogeneously across the population.…”
Section: Heterogeneity In Exposure Susceptibility and Transmissionmentioning
confidence: 99%
“…Over the course of the SARS-CoV-2 pandemic, whole genome sequencing has been widely used to characterize patterns of broad geographic spread, transmission in local clusters, and the spread of specific viral variants 1 6 . Early reports demonstrated that SARS-CoV-2 exhibits genetic diversity within infected hosts, but this has been less studied than consensus-level genomic diversity 7 .…”
Section: Introductionmentioning
confidence: 99%